2019
DOI: 10.1002/jcsm.12399
|View full text |Cite
|
Sign up to set email alerts
|

Muscle mass determined from urinary creatinine excretion rate, and muscle performance in renal transplant recipients

Abstract: Background Muscle mass, as determined from 24‐h urinary creatinine excretion rate (CER), is an independent predictor for mortality and graft failure in renal transplant recipients (RTR). It is currently unknown whether CER is comparable with healthy controls after transplantation and whether it reflects muscle performance besides muscle mass. We aimed to compare urinary CER and muscle performance between RTR and healthy controls and to investigate whether urinary CER is associated with muscle perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 48 publications
1
30
1
Order By: Relevance
“…Given the high rate of obesity in our cohort (27%), the prevalence of low muscle mass by use of BIA is probably underestimated in this study population. In addition to the recommended body c Due to incomplete 24-h urine samples or missing data the number (N) available for analysis for creatinine clearance was N ¼ 536, for proteinuria N ¼ 502, for 24-h creatinine excretion N ¼ 534, for 24-h sodium excretion rate N ¼ 534, for 24-h potassium excretion rate N ¼ 520 and for protein intake (24-h urea excretion) N ¼ 501. composition measures, when applied properly, 24-h urinary CER is a reliable non-invasive method to assess muscle mass in the general population and RTR [21,22,59]. However, validated age-and gender specific cut-off values for low muscle mass based on 24-h CER are not yet available, which hampers its clinical use for the diagnosis of malnutrition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the high rate of obesity in our cohort (27%), the prevalence of low muscle mass by use of BIA is probably underestimated in this study population. In addition to the recommended body c Due to incomplete 24-h urine samples or missing data the number (N) available for analysis for creatinine clearance was N ¼ 536, for proteinuria N ¼ 502, for 24-h creatinine excretion N ¼ 534, for 24-h sodium excretion rate N ¼ 534, for 24-h potassium excretion rate N ¼ 520 and for protein intake (24-h urea excretion) N ¼ 501. composition measures, when applied properly, 24-h urinary CER is a reliable non-invasive method to assess muscle mass in the general population and RTR [21,22,59]. However, validated age-and gender specific cut-off values for low muscle mass based on 24-h CER are not yet available, which hampers its clinical use for the diagnosis of malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, while standard anthropometric measurements, such as weight and height, are routinely performed at outpatient visits, the assessment of muscle mass, for example with dual energy x-ray absorptiometry (DEXA) or bio-electrical impedance analysis (BIA) as recommended by GLIM, is usually not part of routine care due to practical and time constraints [26]. In several renal transplant care centers, however, 24-h urine samples are routinely collected during outpatient visits, enabling measurement of 24-h urinary creatinine excretion rate (CER), which has shown to be a reliable marker of muscle mass in RTR [21,22]. Therefore, it is worthwhile to explore its potential value for the assessment of reduced muscle mass in diagnosing malnutrition in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, other methods for bedside measurement, such as ultrasound, are gaining interest, but require further investigation [56]. Moreover, 24-h urine collections allow assessment of muscle mass from excretion of creatinine, but are only available in specific settings [57][58][59]. Thus, although additional body composition assessment is required to make an adequate diagnosis of malnutrition, its application in daily practice remains challenging.…”
Section: Discussionmentioning
confidence: 99%
“…To this regard, a large and growing group of patients that might be worthwhile studying is that of renal transplant recipients (RTR), in which protein-energy wasting is always lurking [17][18][19]. In fact, it has been found that the risk of premature mortality in this population is 6-7 times higher compared to the general population [20], and this risk was particularly high in RTR with low muscle mass, as reflected by low 24 h urinary creatinine excretion [21,22]. Recent studies furthermore suggested that 24 h urinary creatinine excretion may be a noninvasive, easily accessible, inexpensive, and direct measurement of total body muscle mass [19], while this measure is often not included in clinical studies to complement the imaging technique armamentarium which is applied for evaluation of muscle mass in observational and clinical intervention studies [23][24][25].…”
Section: Introductionmentioning
confidence: 99%